Decolonizing Tamil for Legitimizing English-Mixing in Tamil - Jathusan, J. (University of Jaffna, 2025)
With the “recognition” of Tamil as “a classical” language and the insecure status of Tamil speakers today due to the accelerating linguistic imperialism of English and nationalist languages like Hindi in India and Sinhala in Sri Lanka, there is a growing antagonism in upper-class Tamil nationalist circles against the mixed (mixing) state of Tamil with other languages, including but not limited to English. In the first part of this paper, I argue that, while there are legitimate concerns for Tamil speaking communities to resist the linguistic imperialism of English (and other languages), resistance along the lines of Tamil nationalism and Tamil purism is itself conditioned by the linguistic essentialism and other essentialist ideas of British indirect rule.
The second part of this paper focuses on the attempts made by Tamil purists to do away with English influence in Tamil by introducing a new and supposedly uncontaminated Tamil vocabulary to replace English-origin words in Tamil and by depreciating Tanglish scripts. I argue that, contrary to the claim that the supposedly pure form of Tamil will help the “Tamil national” subjects authentically express themselves, the form of Tamil advocated for by purists appears alien to the usual Tamil speaker, who is already used to using many English-origin words in Tamil and finds Tanglish script, at least when it comes to social media interactions, easier than Tamil script. I argue, moreover, that linguistic purism focuses on transmitting the supposed past of Tamil into the future at the expense of the present of many a Tamil speaker. In the third part of the paper, I argue that, since decolonization should not be about the return to an atavistic past and cannot be complete without overcoming the parochialism of postcolonial nationalisms, it is not sufficient to recognize merely that the “spread” of English and the subsequent penetration of English into Tamil would not have been possible if not for British colonialism. Rather, decolonization means, linguistically speaking, among other things, foregrounding languages as always undergoing changes in contrast to the colonially rooted essentialist understanding of languages. If so, decolonizing English includes the critique of the colonially rooted essentialist understanding of Tamil and, thus, legitimizing at least some forms of English-mixing with Tamil. I conclude my paper by pointing out that my arguments imply that the conflicts between Tamil and other South Asian languages that Tamil comes into contact with should be scrutinized with regard to how colonialism has formed and/or animated such antagonisms.
Keywords: Linguistic essentialism; Nationalism; Purism; Tanglish; Decolonization